2015
DOI: 10.1021/acs.cgd.5b00349
|View full text |Cite
|
Sign up to set email alerts
|

Coamorphous Lurasidone Hydrochloride–Saccharin with Charge-Assisted Hydrogen Bonding Interaction Shows Improved Physical Stability and Enhanced Dissolution with pH-Independent Solubility Behavior

Abstract: Recently, coamorphous systems, composed of a drug and a guest molecule, have gained increasing interest, due to their ability to overcome limitations associated with amorphous drug alone. In this study, a single-phase coamorphous form of lurasidone hydrochloride (LH) (a water-insoluble atypical antipsychotic agent with pH-dependent solubility) with saccharin (SAC) in a 1:1 molar ratio was obtained and characterized by differential scanning calorimetry and powder X-ray diffraction. Peak shifts in the Fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 49 publications
2
74
0
Order By: Relevance
“…The aim of the current study was to improve the dissolution properties of the poorly watersoluble OL via formation of stable OL co-amorphous dispersions (COADs) from successful solid dispersions with some polycarboxylic acids (CAPs) . Solid dispersion method adjustment could result in co-amorphization of the active pharmaceutical ingredients using numerous coformers and many successful examples were employed in the pharmaceutical research for improving the physicochemical properties especially for poorly soluble drugs Qian et al, 2015). Co-milling and freeze drying with hydrophilic polymers were used to form amorphous glass solutions and hot-melt extrusion of drugs using mixtures of low-melting polymers and surfactants were also employed for co-amorphization (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the current study was to improve the dissolution properties of the poorly watersoluble OL via formation of stable OL co-amorphous dispersions (COADs) from successful solid dispersions with some polycarboxylic acids (CAPs) . Solid dispersion method adjustment could result in co-amorphization of the active pharmaceutical ingredients using numerous coformers and many successful examples were employed in the pharmaceutical research for improving the physicochemical properties especially for poorly soluble drugs Qian et al, 2015). Co-milling and freeze drying with hydrophilic polymers were used to form amorphous glass solutions and hot-melt extrusion of drugs using mixtures of low-melting polymers and surfactants were also employed for co-amorphization (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…22 To date, most studies with coamorphous systems reporting the extent of solid-state stability upon storage have observed physical stability for days, weeks, and months. For example, a 1:1 molar ratio of coamorphous sulfathiazoleetartaric acid remained stable for 28 days at room temperature and 10% RH, 23 a 1:1 molar ratio of lurasidone hydrochlorideesaccharin remained stable for 60 days at 25 C/60% RH, 24 and a 1:1 molar ratio of repaglinide-saccharin remained stable for 3 months at 40 C/75% RH. 25 It has been shown that a 1:1 molar ratio of coamorphous indomethacin-lysine remained stable for 10 months under dry conditions 26 and room temperature, while naproxen-arginine and naproxen-tryptophan remained stable for 332 days at room temperature and 40 C under dry conditions.…”
Section: Physical Stabilitymentioning
confidence: 99%
“…Differences in drug crystals in pre-formulation study including polymorphism, crystal morphology, or habit significantly affect not only manufacturing processes but also pharmaceutical properties of final products, such as dissolution, physical and chemical stabilities, powder flow, bulk handling, ease of compression, and wettability. [1][2][3][4][5][6] For the development of drugs with superior pharmaceutical properties, it is important to select an appropriate drug polymorph and to control their transformation and morphology. In addition, recent efforts in solid pharmaceutics have refocused on the development of drugs in amorphous form to improve the oral bioavailability of poorly water-soluble drugs because this confers a high supersaturation solubility to the drugs.…”
Section: Introductionmentioning
confidence: 99%